Brake failure detection and electronic auxiliary braking system - Deepa, N.; Dasmunshi, Sanchayita; Verma, Shubhangi; Shukla, Anurag; Nanda, Sneha (International Journal of Engineering and Technology, 2018)
Brakes are the integral part of a vehicle, which are used to reduce the speed of the car. Brake failure is one of the major problems, which lead to several accidents. Brake failure occurs due to brake lining fails, which leads to pressure loss. This mainly occurs in pneumatic brakes, which are used in most of the vehicles. The aim of our paper is to diagnose the faulty braking system and to enable the functioning of auxiliary braking or secondary brake system during brake failure. When the primary pneumatic brake fails the pressure sensor detects the brake failure and gives warning signal to the driver and also enables the auxiliary brake, which can be controlled by the driver manually through a manual control board. This braking system ensures the safety of the driver as well as the passengers without causing any damage to the vehicle.